Phototunable Liquid‐Crystalline Phases Made of Nanoparticles1. (8th October 2014) - Zep, Anna; Wojcik, Michal M.; Lewandowski, Wiktor; Sitkowska, Kaja; Prominski, Aleksander; Mieczkowski, Jozef; Pociecha, Damian; Gorecka, Ewa
Abstract The properties of liquid‐crystalline (LC) hybrid systems made of inorganic nanoparticles grafted with photosensitive azo compounds are presented. For materials with a large density of azo ligands at the surface, the LC structure can be reversibly melted by UV light, and the return to the LC state does not require the absorption of visible light. For systems with a lower density of azo ligands, UV light causes shortening of the distance between metal sublayers in the lamellar phase. Interestingly, the azo derivatives attached to the nanoparticle surface show very different kinetics of cis/trans conformational change as compared to the free molecules. The cis form of free ligands in solution is stable for days, whereas the isomerization of molecules attached to the nanoparticle surface to the trans form takes only a few minutes. Apparently, owing to the crowded environment, azo ligands immobilized at a metal surface behave as they would in the condensed state.